ECONOMIC AND ENVIRONMENTAL IMPACTS OF BLOOD TRANSFUSIONS: PATIENT BLOOD MANAGEMENT (PBM) AS A PATHWAY TO SUSTAINABILITY - Yago Beserra Marinho Martins; Deyvson Rodrigues Cavalcanti (Artefactum - revista de estudos interdisciplinares, 2026)
While blood transfusion remains a cornerstone of modern medicine, it often masks a complex reality of clinical risks, escalating hospital costs, and an under-examined environmental footprint. This theoretical essay reconsiders Patient Blood Management (PBM) beyond its traditional role as a safety guideline, repositioning it as a fundamental strategy for systemic sustainability in healthcare. By integrating PBM with the principles of Planetary Health, we explore how the judicious reduction of allogeneic transfusions and the rationalization of diagnostic testing offer a triple advantage: enhanced patient safety, fiscal efficiency, and a reduced carbon footprint. The evidence suggests that moving away from the paradigm of indiscriminate transfusion does more than improve clinical outcomes; it provides the resilience healthcare systems need to navigate sanitary and logistical crises, which are increasingly exacerbated by climate change. Ultimately, this work argues that the implementation of PBM transcends mere technical management; it is an ethical imperative that aligns individual patient care with the urgent responsibility of preserving the ecosystems upon which human health depends.